Effectiveness of Competency-Based Training for construction Labor in West Sumatra - Jumas, Dwifitra Yenti; Ariani, Vivi; Asrini, Asirini (Jurnal Rekayasa Sipil (JRS-Unand), 2021)
The issuance of Minister Regulation of Public Works and Public Housing (PUPR) No. 24/ PRT/ M/ 2014 concerning Competency-Based Training Guidelines in the Construction Services Sector is a strong effort by the government to increase the capacity of sustainable construction human resources in order to produce productive and competent human resources. Therefore, the workforce must-have requirements and a series of specific competencies to carry it out effectively and efficiently. Moreover, these competencies must be under the work they will do. The Kirkpatrick Model is used to evaluate the results of training and learning programs and rates against four levels of criteria: reaction, learning, behavior, and results. This research aims to find out what variables affect the effectiveness of competency-based training based on Kirkpatrick's four levels and see whether the competency training activities effectively increase human resources in construction services. A total of 64 questionnaires were then distributed to relevant respondents who attended the competency-based training held in West Sumatera during the 2017-2018 periods. From the results, there are 4 Kirkpatrick level variables that affect the effectiveness of training, namely the level of reaction (21 indicators), learning (6 indicators), behavior (7 indicators), and results (11 indicators). The variable that shows the most effective results is the variable level of learning as much as 47.51%, followed by results (44.56%), learning (47.51%), and behavior (29.27). It can be concluded thatÂ  the workforce competency training conducted in West Sumatera from 2017 to 2018 was still less effective.